Report of the National Food and Nutrition Coordinating Committee of Jamaica (National Food and Nutrition Coordinating Committee ofJamaica KingstonJM, 1986)
Reviews development of the Committee. Discusses the food and nutrition situation in Jamaica focusing on national food supply, household food availability, and nutritional status of the nation. Outlines work plan activities for 1985/86 which comprises a brief discussion of the approach and emphasis and a description of projects by activity areas such as programming, mass communication, seminars, workshops, in-service training, research, and publications. Contains a brief discussion of work plan and schedule of activities agreed upon for 1986/87 the details of which are shown in annexes iii and iv respectively.
Inaugural annual report